An integrated flood management system based on linking environmental models and disaster-related data. (May 2017) - Qiu, Linyao; Du, Zhiqiang; Zhu, Qing; Fan, Yida
Abstract: The flood disaster management system (FDMS) is a platform developed to provide ongoing disaster reduction capabilities that cover the entire process of flood management. The ontology-based approach links environmental models with disaster-related data to support FDMS-constructed workflows with suitable models and recommend appropriate datasets as model input automatically. This automated activity for model selection and data binding reduces the time-consuming and unreliable operations involved in traditional management techniques, which rely on manual retrieval through simple metadata indices—typically when flood management personnel are overwhelmed with large quantities of observed data. The OpenMI-based modular design used in the system unifies interfaces and data exchange to provide flexible and extensible architecture. Subsequent 3D visualization improves the interpretability of disaster data and the effectiveness of decision-making processes. This paper presents an overview of the design and capabilities of FDMS that provides one-stop management for flood disasters. Highlights: The system provides ongoing disaster mitigation capabilities in the entire process of flood management. The linking approach improves the automated activity for model selection and data finding in flood reduction. OpenMI-based modular architecture supports flexible workflow construction and functional extension. A variety of 3D visualization tools improve the interpretability of flood information.